Renal cell carcinoma with MiTF/TFE3 translocation in children: Report of a case at the stage of lymph node involvement - Boubacar Fall; Alioune Sarr; Yaya Sow; Babacar Diao (Wolters Kluwer Medknow Publications, 2011)
Renal cell carcinoma (RCC) is rare in children. Unlike nephroblastoma, however, it does not respond well to chemoradiotherapy. Its treatment is therefore based on surgical removal of the tumour. However, lymphadenectomy for RCC is controversial, and its prognosis is unclear. The authors report a case of RCC with MiTF/TFE3 translocation at the stage of lymph node involvement without metastasis in a boy of age 12, who was treated with radical nephrectomy and limited lymphadenectomy. This tumour constitutes a newly individualised entity in the World Health Organization's 2004 classification. Eighteen months after the operation, the patient was presented with no sign of recurrence. This case aids in showing that lymph node involvement in RCC with translocation in children is not associated with a poor prognosis and that lymphadenectomy during surgery for enlarged nephrectomy is essential.